Gastrointestinal parasites in tagua (Catagonus wagneri) raised at the Chaco Center for Conservation and Research, Paraguay - Gómez, Raquel (2024)
The Chaco peccary or tagua lives in the Paraguayan Chaco and is on the red list of the International Union for Conservation of Nature (IUCN) and on the red list of Paraguay as an endangered animal. Therefore, the aim of this work was to identify gastrointestinal parasites in tagua, determining possible associations between parasite load and population densities in captive tagua pens of the Chaco Center for Conservation and Research. Faecal samples were collected from animals and pooled according to pens and subjected to analysis using the sugar flotation technique. The presence of Ascaris spp, Coccidea spp and cestodes was found, but without being able to determine the species. The parasitic infestation was independent of the population density of the pens (p>0.05).